2019
DOI: 10.1038/s41598-018-37419-4
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic endfeet re-cover blood vessels after removal by laser ablation

Abstract: The astrocyte, one of the glial cells, plays many functional roles. These include provision of nutrients from blood vessels to neurons, supply of neurotransmitters and support of blood–brain barrier (BBB) integrity. Astrocytes are known to support the integrity of BBB through maintenance of the tight junction between endothelial cells of blood vessels. However, evidence of its direct contribution to BBB is lacking owing to technical limitations. In this study, astrocytic endfeet covering blood vessels were rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 43 publications
2
72
0
1
Order By: Relevance
“…In addition to microglial analysis, we examined the protective effects of moderate physical exercise on vessel coverage by astrocytes in animals with chronic cerebral hypoperfusion. These cells are part of the neurovascular unit and BBB, playing a key role in the structure of the BBB, in the communication with neurons, glutamate homeostasis [62], and also stimulating the release of vasoactive compounds in microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microglial analysis, we examined the protective effects of moderate physical exercise on vessel coverage by astrocytes in animals with chronic cerebral hypoperfusion. These cells are part of the neurovascular unit and BBB, playing a key role in the structure of the BBB, in the communication with neurons, glutamate homeostasis [62], and also stimulating the release of vasoactive compounds in microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of astrocytes into nonneural tissues of adult rats induces barrier properties in local ECs (Janzer and Raff, 1987), and several astrocyte-secreted proteins are sufficient to induce EC barrier properties in vitro and in vivo, including Sonic hedgehog, angiotensin, and basic fibroblast growth factor (Alvarez et al, 2011; Sobue et al, 1999; Wosik et al, 2007). However, barrier properties arise during development before astrogliogenesis takes place (Ben-Zvi et al, 2014; Daneman et al, 2010a; Sohet et al, 2015; Sauvageot and Stiles, 2002), delaying astrocytic contact with ECs does not affect barrier formation (Saunders et al, 2016), and laser ablation of astrocyte endfeet in adult mice does not induce BBB leakage (Kubotera et al, 2019). These data suggest that astrocytes are not necessary for BBB formation, but perhaps provide dynamic BBB regulation in response to specific stimuli.…”
Section: Bbb Formation and Regulationmentioning
confidence: 99%
“…One study concluded that there were no changes to the BBB based on the absence of leakage of Evans Blue (960 Da when unbound and 65-70 kDa when bound to albumin) and dextran (4 kDa) after laser ablation of astrocytes or endfeet followed by 2-photon imaging (Kubotera et al, 2019). Yet cell death was only confirmed by lack of a fluorescent eGFP signal, which can occur as a result of photobleaching after which the still-alive cell is no longer visible.…”
Section: Astrocyte Loss In the Adult Brain Causes Bbb Damage Of Variamentioning
confidence: 99%
“…Alternatively, it is possible that ablation of a single astrocyte or single endfoot is not sufficient to induce BBB damage and that secreted factors by neighboring cells are sufficient to maintain barrier integrity. Integrity of tight junctions and other barrier properties were not assessed in this study (Kubotera et al, 2019).…”
Section: Astrocyte Loss In the Adult Brain Causes Bbb Damage Of Variamentioning
confidence: 99%
See 1 more Smart Citation